Borrelia burgdorferi regulates expression of complement regulator-acquiring surface protein 1 during the mammal-tick infection cycle - Lackum, Kate von; Miller, Jennifer C.; Bykowski, Tomasz; Riley, Sean P.; Woodman, Michael E.; Brade, Volker; Kraiczy, Peter; Stevenson, Brian; Wallich, Reinhard (Infection and immunity, 2005)
During the natural mammal-tick infection cycle, the Lyme disease spirochete Borrelia burgdorferi comes into contact with components of the alternative complement pathway. B. burgdorferi, like many other human pathogens, has evolved the immune evasion strategy of binding two host-derived fluid-phase regulators of complement, factor H and factor H-like protein 1 (FHL-1). The borrelial complement regulator-acquiring surface protein 1 (CRASP-1) is a surface-exposed lipoprotein that binds both factor H and FHL-1. Analysis of CRASP-1 expression during the mammal-tick infectious cycle indicated that B. burgdorferi expresses this protein during mammalian infection, supporting the hypothesized role for CRASP-1 in immune evasion. However, CRASP-1 synthesis was repressed in bacteria during colonization of vector ticks. Analysis of cultured bacteria indicated that CRASP-1 is differentially expressed in response to changes in pH. Comparisons of CRASP-1 expression patterns with those of other infection-associated B. burgdorferi proteins, including the OspC, OspA, and Erp proteins, indicated that each protein is regulated through a unique mechanism.
Gesehen am 07.06.2021